Total Synthesis of Tagetitoxin - He, Chi; Chu, Hang; Stratton, Thomas P; Kossler, David; Eberle, Kelly J; Flood, Dillon T; Baran, Phil S (Journal of the American Chemical Society, 2020)
The intriguing structure of tagetitoxin (1), a long-standing challenge in natural product synthesis, has been the subject of multiple revisions and has been confirmed through total synthesis. The route commences from a renewable furan starting material and features a number of unusual transformations (such as rearrangements, bromocyclization, and P(V)-based phosphate installation) to arrive at the target in 15 steps. As the route was designed to enable access to both enantiomers, the absolute configuration of the natural product could be assigned using a bioassay on (+)-1 and (−)-1.